PENANAMAN NILAI PESANTREN DALAM PEMBENTUKAN KARAKTER ANAK - Linda Kartika Sari; Iva Inayatul Ilahiyah; Ali Said (EL-Islam, 2021)
Character building has become a national issue because many children of the nation show signs of moral degradation; hence, character education is considered to be very instrumental in resolving this nation’s problems. The book Adab al-‘Alim Wa al-Muta‘allim by KH. Hasyim Asy’ari in which the typical values of pesantren are embedded which can help shape the good character of the child. The questions that want to answer through this research are: How to plant pesantren values in the formation of children’s character in the Adab al-‘Alim Wa al-Muta‘allim? This study uses a type of library research. The approach used in this study is a descriptive analysis approach. From the results of the analysis, it was found that the values of the pesantren in the Adab al-‘Alim Wa al-Muta‘allim were: student ethics towards themselves, to teachers, and their lessons. As for character building in the book, students have a sense of responsibility, discipline, perseverance, honesty, independence, hard work, respect, curiosity, willingness to sacrifice, and never give up. This research is expected to be useful for students to have noble character and for teachers to be able to teach and facilitate children to have good character.